Pressure-Induced Crystallization and Phase Transformation of Para-xylene - Yanzhi Bai (Nature Portfolio, 2017)
Abstract Static pressure is an alternative method to chemical pressure for tuning the crystal structure, bonds, and physical properties of materials, and is a significant technique for the synthesis of novel materials and fundamental research. In this letter, we report the crystallization and phase transformation of p-xylene under high pressure. Our optical micrographic observations and the appearance of lattice modes in the Raman and infrared (IR) spectra indicated that p-xylene crystallizes at ∼0.1 GPa. The X-ray diffraction (XRD) pattern at 0.84 GPa suggests that the crystallized p-xylene had a monoclinic phase with the Cc(9) space group. The sharp shrinkage of the lattice at ~13 GPa and the solid state of the decompressed sample we observed suggests a new crystalline phase of p-xylene. The in situ XRD showed that the new crystalline phase was still a monoclinic structure but with a different space group of C2(5), indicating that a phase transition occurred during further compression. The mass spectrometry experiment confirmed phase transition polymerization, with mainly trimer and tetramer polymers. Our findings suggest an easy and efficient method for crystallizing and polymerizing p-xylene under high pressure.